Rethinking Systematic Literature Reviews: A Critical and Evolving Perspective on the SPAR-4-SLR Protocol - BENNANI, Mohamed Hamza; HELMI , Driss (Revue Internationale des Sciences de Gestion, 2025)
Systematic literature reviews have become a key methodological standard in contemporary management research. Yet, in light of the growing diversity of research topics, methodological approaches and contextual realities, the question arises: should the systematic review protocol be reconsidered? This article provides a critical and constructive analysis of the SPAR-4-SLR protocol (Scientific Procedures and Rationales for Systematic Literature Reviews), which has gained significant traction in recent years. Through an in-depth examination of its structure, applications and limitations, we advocate for its evolution into an enriched, modular and reflexive framework: the SPAR+. Our contribution combines a structured typology of review forms, an analysis of existing analytical grids, and a conceptual proposal integrating epistemological positioning, contextual sensitivity, and the opportunities brought by artificial intelligence. This article aims to support scholars, doctoral candidates and journal editors in fostering transparency, rigor, and critical awareness in systematic literature reviews.